ROMANIAN ADMINISTRATIVE-TERRITORIAL UNITS IN FINANCIAL CRISIS - MELINDA CENUŞE (Annals of the University of Petrosani: Economics)
The nowadays economic and financial crisis seems to be unprecedented. We consider that financial crisis of administrative-territorial units is related to global economic crisis and reflects a deregulation of market mechanisms, having, in the same time, some particularities. So, we can see that financial crisis can be felt not only in private sector, but also in public sector, especially in the administrative-territorial units. The financial crisis of administrative-territorial units represents that situation, when its patrimony is characterized by the existence of financial difficulties and the severe shortage of cash, which leads to non-payment of amount liabilities, during a certain time period. In this article we try to present a few legislative aspects regarding the financial crisis of Romanian administrative-territorial units.